Cysteine‐rich intestinal protein 1 enhances the progression of hepatocellular carcinoma via Ras signaling - Hong‐Yu He; Li Hu (Kaohsiung Journal of Medical Sciences, 2022)
Abstract The present study aimed to explore the expression and clinical significance of cysteine‐rich intestinal protein 1 (CRIP1) mRNA in the serum of patients with hepatocellular carcinoma (HCC). Reverse transcription polymerase chain reaction (RT‐PCR) was performed to explore the level of CRIP1 mRNA in the tissues and serum of patients with HCC. Our data showed that the mRNA level of CRIP1 was significantly elevated in the serum and tissues of HCC patients. Moreover, serum CRIP1 mRNA was significantly elevated in HCC patients with larger tumor sizes and higher tumor node metastasis (TNM) stages. Receiver operating characteristic analysis showed that compared with a single marker, the combined detection of alpha‐fetoprotein, carcinoembryonic antigen, and CRIP1 had the highest accuracy, sensitivity, and specificity. Further study showed that the overexpression of CRIP1 enhanced the proliferation and migration of HepG2 cells, but the inhibition of CRIP1 decreased the proliferation and migration of HepG2 cells. Microarray assays and KyotoEncyclopedia of Genes and Genomes (KEGG) pathway analysis showed that overexpression of CRIP1 induced the activation of Ras signaling. Co‐immunoprecipitation (Co‐IP) assays indicated that CRIP1 could interact with Ras. To further evaluate whether CRIP1 interacts with Ras, a specific siRNA targeting Ras was selected. We found that Ras knockdown reduced the activation of Ras/AKT signaling even in HepG2 cells transfected with CRIP1. Moreover, elevated expression of CRIP1 increased the proliferation of HepG2 cells, but such effects could be abolished by silencing Ras. In summary, elevated CRIP1 levels enhanced the progression of CRIP1 via Ras signaling.